Hubungan antara ketegasan diri dan kepuasan hidup dalam kalangan pelajar institusi pengajian tinggi - Salleh Amat; Zuria Mahmud (penerbit ukm, 2009)
This paper reports a study that investigates the relationship between assertiveness and satisfaction with life among students at a higher learning institution. One hundred and seventy undergraduate students (second and first year students) studying an introductory counseling course voluntarily participated in this study. Two sets of instruments: The Rathus Assertiveness Schedule and the Satisfaction with Life Scale were translated into Malay language to measure assertiveness and satisfaction with life. The finding shows a significant relationship between assertiveness and satisfaction with life. Nevertheless, assertiveness and satisfaction with life are not significantly related with academic achievement. In addition, the level of assertiveness and satisfaction with life among 2 and 3 Year students are not significantly different. Implications of the study on students at higher learning institutions are discussed in this report.